The association between insulin resistance, metabolic syndrome, and ischemic heart disease among Rumoi residents. (15th June 2017) - Tan, Ce; Sasagawa, Yutaka; Mori, Mitsuru
Abstract: Background: It has widely been proven that metabolic syndrome (MetS) increases the risk of ischemic heart disease (IHD). MetS is confirmed based upon insulin resistance (IR). Our aim of this study is to evaluate the role of MetS and IR in the prediction of IHD incidence. Methods: A total of 404 non‐diabetic participants who underwent 75 g oral glucose tolerance test (75 g OGTT) were enrolled from 2001 to 2009. Risk factors for IHD were measured as well. The homeostatic index of IR (HOMA‐IR) and the homeostatic model assessment beta cell function (HOMA‐β) were calculated according to the homeostasis model assessment. Cox proportional‐hazard regression model was used to estimate hazard ratio (HR). All data were analyzed using SPSS 21 software (IBM, Armonk, NY, USA). Results: In our study, the average follow‐up period was 6.7 years. Eighteen subjects of IHD incidence were recorded. After adjusting for age and sex, subjects with IR or hyperinsulinemia had a high risk of IHD, the hazard ratio (95% confidence intervals) for IHD were 4.58 (1.59‐13.15), 4.25 (1.64‐11.91), respectively. The highest hazard ratio was 7.56 (2.27‐25.18) which was found among the subjects with both IR and hyperinsulinemia. In addition, the hazard ratio (95% confidence intervals) of subjects with MetS was 2.80(1.10‐7.09). Conclusions: IR and hyperinsulinemia are related to the risk of IHD. IR combined with hyperinsulinemia may be superior to MetS for predicting the IHD incidence.